Markets as Dualistic, Semi-Decentralized Organizations - William A. Jackson (Review of Evolutionary Political Economy, 2024)
The theoretical ideal of a competitive market is generally assumed to separate organizing from trading, in an implicit dualism. Traders sell or buy within the market but do not organize it. This paper proposes an alternative, more realistic conceptual scheme based on duality, in which organizing and trading are distinct but intertwined. While the exchange of property rights is overseen centrally, many details of market trade are decided locally by traders. Producers and retailers may arrange the trading venue, specify the items traded, set and publish prices, provide information, and transport goods. They cultivate relationships with customers, recasting the pattern of trade and the social structures that underlie the market. Such dualistic, semi decentralized organizing generates other dualities, including stability-change and continuity-creativity. A duality perspective can encompass the complexity of markets, as well as illustrating the numerous ways they may evolve.
Keywords: B52; D40; L11; L14; 330; markets; organization; duality; complexity; evolution